Construction of Generalized Neighbor Designs in Circular Blocks of Two Different Sizes - Mehmood, Q.; Nadeem, M.; Noreen, K.; Ahmad, R. (The Nucleus, 2022)
Neighbor balanced designs are used in experiments where neighbor effects may arise. These designs ensure that treatment comparisons will be less affected by the neighbor effects. Experimenters always prefer minimal designs but minimal circular neighbor designs cannot be constructed for even v, where v is number of treatments to be compared. Therefore, for v even, minimal circular generalized neighbor designs (MGNDs) should be used which are considered to be the good alternate to the minimal neighbor designs. In this article, some generators are developed to obtain MCGNDs in which 3v/2 unordered pairs of distinct treatments appear twice as neighbors while others appear once. Catalogues of the designs provide readymade solutions to the experimenters and researchers. The proposed designs catalogues are also compiled from the generators developed in this study for v (even) ≤ 100.